Intestinal Microbiota - An Unmissable Bridge to Severe Acute Pancreatitis-Associated Acute Lung Injury - Wang, Zhengjian; Li, Fan; Liu, Jin; Luo, Yalan; Guo, Haoya; Yang, Qi; Xu, Caiming; Ma, Shurong; Chen, Hailong (Frontiers in Immunology, 2022)
Severe acute pancreatitis (SAP), one of the most serious abdominal emergencies in general surgery, is characterized by acute and rapid onset as well as high mortality, which often leads to multiple organ failure (MOF). Acute lung injury (ALI), the earliest accompanied organ dysfunction, is the most common cause of death in patients following the SAP onset. The exact pathogenesis of ALI during SAP, however, remains unclear. In recent years, advances in the microbiota-gut-lung axis have led to a better understanding of SAP-associated lung injury (PALI). In addition, the bidirectional communications between intestinal microbes and the lung are becoming more apparent. This paper aims to review the mechanisms of an imbalanced intestinal microbiota contributing to the development of PALI, which is mediated by the disruption of physical, chemical, and immune barriers in the intestine, promotes bacterial translocation and results in the activation of abnormal immune responses in severe pancreatitis. The pathogen-associated molecular patterns (PAMPs) mediated immunol mechanisms in the occurrence of PALI via binding with pattern recognition receptors (PRRs) through the microbiota-gut-lung axis are focused. Moreover, the potential therapeutic strategies for alleviating PALI by regulating the composition or the function of the intestinal microbiota are discussed in this review. It is expected to provide new thoughts and therapeutic tools for PALI patients in the future.